2005
DOI: 10.1080/j.1440-1614.2005.01608.x
|View full text |Cite
|
Sign up to set email alerts
|

Relative Contributions of Psychiatric Symptoms and Neuropsychological Functioning to Quality of Life in First-Episode Psychosis

Abstract: Objective: To report on the relationship between quality of life (QOL), psychiatric symptoms and neuropsychological functioning in a sample of young people who have experienced a first episode of psychosis 2-3 years following initial presentation. Method: Fifty-one participants aged 15-27 years old completed the short form of the World Health Organization Quality of Life scale (WHOQOL-Brèf), a self-report instrument assessing physical, psychological, social and environmental aspects of QOL. A comprehensive neu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
23
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(28 citation statements)
references
References 27 publications
4
23
1
Order By: Relevance
“…An analysis of covariance (ANCOVA) was used to compare the suicidal and non-suicidal groups on SQOL ratings. Depressive symptoms that have been associated with SQOL and suicidal behavior in previous research [9,42,43] were included as a covariate in comparison analyses. To investigate possible risk factors, we used binary logistic regression (Wald) forward stepwise analysis for prediction of lifetime suicide attempts and present suicidal ideations.…”
Section: Discussionmentioning
confidence: 99%
“…An analysis of covariance (ANCOVA) was used to compare the suicidal and non-suicidal groups on SQOL ratings. Depressive symptoms that have been associated with SQOL and suicidal behavior in previous research [9,42,43] were included as a covariate in comparison analyses. To investigate possible risk factors, we used binary logistic regression (Wald) forward stepwise analysis for prediction of lifetime suicide attempts and present suicidal ideations.…”
Section: Discussionmentioning
confidence: 99%
“…Negative symptoms are; however, closely related to the associated outcomes studied in the current review. For example, Wegener et al (2005) reported that 43% of the variance in quality of life measures among those with psychosis can be explained by levels of depression, general psychopathology and negative symptoms, while several longitudinal studies support the notion that negative symptoms are important determinants of quality of life in those with psychosis (Ho, Nopoulos, Flaum, Arndt, & Andreasen, 1998;Priebe, Roeder-Wanner, & Kaiser, 2000). We therefore reiterate our call for further research to develop and test the efficacy of self-help interventions targeting the negative symptoms of psychosis, as such interventions may be most likely to influence outcomes.…”
Section: P R E P U B L I C a T I O N C O P Ymentioning
confidence: 99%
“…Some studies demonstrated that cognitive dysfunction had a greater influence on schizophrenia patients' QOL than positive symptoms (33)(34)(35). On the other hand, some reported that neuropsychological function had a little impact on their QOL in the presence of some clinical symptoms (32,36). The discrepancy among these studies might have been caused by differences of sample population, cognitive tests, and QOL scales (32)(33)(34)36).…”
Section: Relation Between Cognitive Func-tion and Quality Of Lifementioning
confidence: 99%